PENGGUNAAN METODE READ ALOUD DALAM MEMBANTU KESULITAN BELAJAR DISLEKSIA TERHADAP SISWA - Muchlinarwati Muchlinarwati (lembaga Sepercenter, 2024)
Learning is a process of teaching and learning activities and plays a role in determining student success. From this learning there will be a reciprocal activity between teachers and students to achieve better goals. This research aims to enhance storytelling ability implemented by Read Aloud method. This is a classroom action research (CAR). It consist of two cycles. Each cycle conducted of four phase, namely planning, action, observation, and reflection. Data collection technique conducted by observation, interview, documentation, field note, and performance test. The data validity test were source triangulation and method triangulation. It used descriptive comparative and critical analytic as data analysis. The result indicated that the implementation of Read Aloud method could be able to enchance the storytelling ability and also the effectiveness of learning study PAI.